ONZIN Upregulation by Mutant p53 Contributes to Osteosarcoma Metastasis Through the CXCL5-MAPK Signaling Pathway - Yanqin Zhang; Qianghua Hu; Guixin Li; Lili Li; Shoulei Liang; Yun Zhang; Jiayong Liu; Zhengfu Fan; Lin Li; Bingzheng Zhou; Yongxin Ruan; Xueli Yang; et al. (Cellular Physiology and Biochemistry, 2018)
Background/Aims: Gain-of-function of mutant p53 is associated with a high rate of lung metastasis in osteosarcoma. To investigate the mechanism of mutant p53-induced osteosarcoma metastasis, expression array analysis was performed, comparing non-metastatic osteosarcomas from p53+/- mice with metastatic osteosarcomas from p53R172H/+ mice. Onzin (Plac8) was identified as one of the genes upregulated in p53R172H/+ mouse metastatic osteosarcomas. Accordingly, we investigated the role of ONZIN in human osteosarcoma metastasis. Methods: ONZIN function and its downstream targets were examined in osteosarcoma cell lines. Assays related to tumorigenesis and metastasis, including cell migration, invasion, clonogenic survival, and soft agar colony formation, were performed in osteosarcoma cells. Additionally, mouse xenograft models were used to examine the role of ONZIN overpression in tumorigenesis in vivo. Lastly, 87 osteosarcoma patients were recruited to investigate the clinical relevance of ONZIN overexpression in metastasis and prognosis. Results: ONZIN overexpression enhanced osteosarcoma cell proliferation, clonogenic survival, migration, and invasion independent of p53 status. Furthermore, ONZIN overexpression induced CXCL5 upregulation and resulted in increased ERK phosphorylation, which contributed to more aggressive osteosarcoma metastatic phenotypes. More importantly, overexpression of ONZIN in human osteosarcoma patients was closely associated with lung metastasis, poor prognoses, and survival. Conclusions: Overexpression of ONZIN promotes osteosarcoma progression and metastasis, and can serve as a clinical biomarker for osteosarcoma metastasis and prognosis.